Health promotion and aging : practical applications for health professionals - Haber, David, 1944- (Springer Pub., 2010)
This fifth edition of Health Promotion and Aging has been substantially revised and updated with multiple new sub-sections, topics, and terms in each chapter. This book presents a wide scope of cutting-edge topics including gay aging, Jewish aging, social networking, brain games, the Obama administration's health care reform, mental health parity, exploritas, Wii-habilitation, elderspeak, skin cancer, Family Smoking Prevention and Tobacco Control Act, Senator Ted Kennedy's government-run long term care proposal, and sleep-related medical disorders. This book is focused on current research findings and practical applications, and includes detailed descriptions of two of the author's own programs that have been recognized by the National Council on the Aging's Best Practices in Health Promotion and Aging.